EVALUASI PENGGUNAAN ANTIBIOTIK DENGAN METODE ATC/DDD DAN PDD DENGAN DU 90% PADA PENDERITA ISPA NON PNEUMONIA DI PUSKESMAS KABUPATEN SAMPANG - Rehmadanta Sitepu; Toni Tri Cahyono; Eva Monica (Jurnal JKFT, 2020)
Irrational use of antibiotics can cause an increase in morbidity and mortality, while also causing resistance to antibiotics. Evaluate the use of antibiotics aimed at reducing the use of antibiotics in ARI Non-Pneumonia as well as supporting government programs that the use of antibiotics for ARI non-pneumonia is no more than 20%. This research is descriptive in nature with a cross-sectional design and retrospective data collection in the January-September 2019 period. The data used are the use of antibiotics in Non-pneumonia ARI in the Sampang Regency. Evaluation of the use of this antibiotic using the ATC / DDD, PDD, PDD and DDD Comparison Ratio as well as 90% DU. There are 7 types of antibiotics used for Non-Pneumonia ISPA and 2 types of antibiotics included in DU90% are amoxicillin 500 mg by 44.63% and ciprofloxacin 500 mg by 44.58%. Quantitative data analysis using ATC / DDD shows that the most widely used antibiotic is amoxicillin 500 mg of 742.58 DDD / 1000 patient-days. Inappropriate use of antibiotics can increase the incidence of resistance. A policy is needed to control the use of antibiotics in Puskesmas to reduce antibiotic resistance and its side effects.